Viaggiare e vivere altrove. Sulla condizione del migrante nel paese d’adozione nel romanzo „M” di Ron Kubati - Karp, Karol (Studia Europaea Gnesnensia, 2018)
Kubati’s novel entitled „M”, in which there is no shortage of autobiographical elements, draws on the experience of migration that the author partook in the early 1990s, having left his homeland for Italy. Where the story takes place is unspecified, though the reader is well aware that it is nowhere else but in Italy. The author takes advantage of his own, extensive knowledge and draws a very comprehensive picture of the migrant’s existential position in a foreign land. This paper, comprising two main parts, aims to analyze that position, striving to delineate the nature of the phenomenon of migration. The first part is devoted to the problems that a migrant is forced to confront. Being lost in a new space, the daily experience of dearth of financial means and acts of racism exacerbate the sense of inferiority and lack of belonging. The second part discusses the process of the migrant’s social integration. With time, the knowledge of the city becomes sufficient to move about with ease, while contacts with its native inhabitants are characterized by kindness and openness. The sojourn in a foreign country proves to be a positive experience, enabling the protagonist to achieve numerous goals and entertain an optimistic outlook on the future.